2022
DOI: 10.1177/10556656221135926
|View full text |Cite
|
Sign up to set email alerts
|

Damaging Mutations in AFDN Contribute to Risk of Nonsyndromic Cleft Lip With or Without Cleft Palate

Abstract: Novel or rare damaging mutations have been implicated in the developmental pathogenesis of nonsyndromic cleft lip with or without cleft palate (nsCL ± P). Thus, we investigated the human genome for high-impact mutations that could explain the risk of nsCL ± P in our cohorts. We conducted next-generation sequencing (NGS) analysis of 130 nsCL ± P case-parent African trios to identify pathogenic variants that contribute to the risk of clefting. We replicated this analysis using whole-exome sequence data from a B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In addition, we identified two variants in AFDN in two separate families, including a novel missense variant in Family 8 (NM_001386888.1: c.3545A > G; NP_001373817.1: p.Asn1182Ser) and an extremely rare splice donor variant in Family 22 (NM_001386888.1: c.1222 + 1G > T). Awotoye et al (2022a) recently reported rare heterozygous and compound heterozygous mutations in AFDN . C onditional deletion of Afdn in the palatal epithelium in mice causes a highly penetrant cleft palate (Lough et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we identified two variants in AFDN in two separate families, including a novel missense variant in Family 8 (NM_001386888.1: c.3545A > G; NP_001373817.1: p.Asn1182Ser) and an extremely rare splice donor variant in Family 22 (NM_001386888.1: c.1222 + 1G > T). Awotoye et al (2022a) recently reported rare heterozygous and compound heterozygous mutations in AFDN . C onditional deletion of Afdn in the palatal epithelium in mice causes a highly penetrant cleft palate (Lough et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In the former category, much work using whole-genome and whole-exome sequencing approaches in patients with CF anomalies have identified several rare genetic variants that contribute to these defects. [63][64][65][66][67] Such genotypedriven diagnosis enables peri-natal risk assessment, early rendering of treatment and enables assessment of disease predilection and future risks. Importantly, the knowledge emerging from studying these rare genetic variants also helps us understand normal and abnormal CF development and provides a mechanistic framework for CF morphogenesis.…”
Section: Omics In Craniofacial Growth Dentofacial Orthopaedics and Or...mentioning
confidence: 99%
“…For example, genes harbouring deleterious variants that result in the described anomalies have been shown to play an essential role in the development of primary and secondary palate, neural crest migration, vasculogenesis, Meckel's cartilage development, retinoic acid pathway and suture fusion. [63][64][65][66][67] As noted in Section 3.2, the utilization of facial surface 3D imaging and computational clustering methods have also facilitated genome-wide association studies (GWAS) linking genetic loci to specific facial features. [54][55][56][57]68,69 To date, several genes have been implicated in skeletal Class II and Class III malocclusions (19 and 53 genes, respectively); these genes are involved in conserved signalling pathways playing a role in bone and cartilage development.…”
Section: Omics In Craniofacial Growth Dentofacial Orthopaedics and Or...mentioning
confidence: 99%
See 2 more Smart Citations